Funkcja słownictwa medycznego w twórczości Stefana Żeromskiego (uwagi wstępne) - Jankowiak, Lucyna Agnieszka (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2015)
Stefan Żeromski was an expert in medical vocabulary. This was a result of his interest in medicine. He used medical vocabulary in his output in its basic function, that is in order to characterize the health of his characters, and in a secondary function. The secondary function involved using medical vocabulary (not only Polish) to describe various phenomena and situations. Among others, he used it to describe the emotional situations of characters; their behaviour and actions, social and political situation, as well as nature, space, objects, literature and art.